Hubungan Dukungan Keluarga dengan Kemampuan Ibu Postpartum Dalam Perawatan Tali Pusat Bayi Baru Lahir Di Wilayah Kerja Puskesmas Gunung Sari Ulu - Puji Handayani,Ari Widyaningsih (STIKes Budi Mulia Sriwijaya, 2024)
Newborn care is care provided to maintain the health of the baby, including proper bathing of the baby and care of the umbilical cord, which can prevent infection and accelerate the release of the umbilical cord. The results of a preliminary study conducted at the Gunung Sari Ulu Health Center obtained data on the number of newborns in 2020: as many as 283 babies; in 2021, there were 216 babies; in 2022, there were 216 babies; and in the January–April 2023 period, there were 72 babies. The results of interviews about family support with 10 postpartum mothers showed that 6 people got good support from their families and 4 people got less support from their families. The results of interviews about umbilical cord care revealed that 3 postpartum mothers understood umbilical cord care and 7 postpartum mothers did not understand umbilical cord care. This study aims to determine the relationship between family support and the ability of postpartum mothers to care for the umbilical cord of newborns in the Working Area of the Gunung Sari Ulu Health Center. This type of research used quantitative research with a descriptive correlational research design and a cross-sectional approach. The study population was postpartum women in the Working Area of the Gunung Sari Ulu Health Center, Balikpapan City, and the sampling technique used a total of 82 people. Collecting data using a questionnaire sheet Data analysis is univariate analysis and bivariate analysis using the chi square test (X2). The description of family support for postpartum mothers is in the high category, namely 42 people (51.2%), and in the low category, namely 40 people (48.8%). The description of the ability of postpartum mothers to care for the umbilical cord of newborns was in the good category, namely 50 people (61%), the sufficient category, namely 28 people (34.1%), and the poor category, namely 11 people (4.9%). Chi square statistical test results (2) obtained a value of (0.017) < α (0.05), indicating that Ha is accepted. Conclusion there is a relationship between family support and the ability of postpartum mothers to care for the umbilical cord of newborns in the Working Area of the Gunung Sari Ulu Health Center.